Biochemical and functional studies of ColTx-I, a new myotoxic phospholipase A2 isolated from Crotalus oreganus lutosus (Great Basin rattlesnake) snake venom. (July 2016) - Almeida, J.R.; Resende, L.M.; Silva, A.G.; Ribeiro, R.I.M.A.; Stábeli, R.G.; Soares, A.M.; Calderon, L.A.; Marangoni, S.; Da Silva, S.L.
Abstract: Commonly, phospholipases A2 (PLA2 s) play key roles in the pathogenesis of the local tissue damage characteristic of crotaline and viperine snake envenomations. Crotalus oreganus lutosus snake venom has not been extensively studied; therefore, the characterization of its components represents a valuable biotechnological tool for studying pathophysiological processes of envenoming and for gaining a deeper understanding of its biological effects. In this study, for the first time, a basic PLA2 myotoxin, ColTx-I, was purified from C. o. lutosus through two chromatographic steps. ColTx-I is monomeric with calculated molecular mass weight (Mw) of 14, 145 Da and a primary structure closely related to basic PLA2 s from viperid venoms. The pure enzyme has a specific activity of 15.87 ± 0.65 nmol/min/mg at optimal conditions (pH 8.0 and 37 °C). ColTx-I activity was found to be dependent on Ca 2+, as its substitution by other ionic species as well as the addition of chelating agents significantly reduced its phospholipase activity. In vivo, ColTx-I triggered dose-dependent inflammatory responses, measured using the paw edema model, with an increase in IL-6 levels, systemic and local myotoxicity, characterized by elevated plasma creatine kinase activity. ColTx-I induced a complex series of degenerative events associated with edema, inflammatory infiltrate and skeletal muscle necrosis. These biochemical and functional results suggest that ColTx-I, a myotoxic and inflammatory mediator, plays a relevant role in C. o. lutosus envenomation. Thus, detailed studies on its mechanism of action, such as evaluating the synergism between ColTx-I and other venom components may reveal targets for the development of more specific and effective therapies. Graphical abstract: Highlights: ColTx-I is a novel basic PLA2 from Crotalus oreganus lutosus snake venom. The primary structure of ColTx-I was determined by LC–MS/MS. ColTx-I triggered both local and systemic myotoxicity. Intramuscular injection of ColTx-I caused mainly necrosis, inflammatory infiltrate and edema. ColTx-I induced dose-dependent inflammation with an increase in IL-6 levels.